Pengaruh E-Service Quality dan E-Trust terhadap E-Satisfaction dan Dampaknya pada E-Repurchase Intention Pengguna Layanan Konsultasi Media Online - Khrisna Ayuningtias, Tyagita; Erliany Syaodih; Wiseto P. Agung (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Apps for telemedicine are becoming increasingly popular as a result of the COVID-19 outbreak. Telemedicine thus competes with other providers to meet patient demand. Many tactics are used to overcome this, such as providing confidence and quality patients. The purpose of this study is to analyze the effect of E-Service Quality and E-Trust on E-Satisfaction and its impact on E-Repurchase Intention on users of Online Medical Consultation Services. This type of research is quantitative. The sample of this study amounted to 100 respondents who had an Online Medical Consultation Service application on a mobile phone and had at least consulted through the application or website at least once. The analysis method used is path analysis. The results of the study show that there is a direct influence between the variables of E-service Quality on E-Satisfaction in users of online medical consultation services. There is a direct influence between E-Trust variables on E-Satisfaction in users of online medical consultation services. There is a direct influence between the variables E-service Quality and E-Trust on E-Satisfaction in users of online consulting services. There is a direct influence between the variables E-service Quality, E-Trust, and E-Satisfaction, on E-Repurchase Intention in users of online medical consultation services. There is an Effect of E-service Quality and E-Trust on E-Satisfaction of 9.9% while the remaining 90.1% (100% - 9.9%) is contributed by other factors. There is an effect of E-service Quality, E-Trust, and E-Satisfaction on E-Repurchase Intention of 34% while the remaining 66% (100% - 34%) is contributed by other factors.